Makarios/Symeon in östlicher Überlieferung : Beiträge des VIII. Makarios-Symposiums, Bergvik 2014 - Tamcke, Martin, 1955- (Göttinger Orientforschungen. Syriaca ;, 2016)
For decades, primarily German and Finnish researchers have been meeting at a symposium where the latest research results and hypotheses on Makarios are discussed. Each symposium sets a thematic focus. The conference takes place alternately in Finland and in Germany. The Bergvik symposium looked at the Eastern reception of Macarios theology and spirituality. At the request of the Finnish colleagues, this time the controversially discussed attempts at the relationship between Macarios and the Koran were also included in the consideration of the Eastern Church's reception (contributions to Byzantium, Russia, Syriac theology and Bulgaria). The volume shows the enormous history of the impact of the Makarios by means of individual aspects and individual reception processes and is therefore more than just a contribution to Makarios research. He provides pieces of the jigsaw puzzle based on the reception of an outstanding thinker of late antiquity on the spiritual world of the orthodox East, which, in addition to the Eastern European traditions, also includes the oriental including the Islamic.